(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The focus of the study is the investigation of terminological foundations and the development of practical recommendations for assessing the effective-ness of hydrocarbon inflow stimulation at the final stage of field development. The authors refer to scientific works on the issues of company performance. The paper provides substantiation and improvement of methodological grounds with respect to assessing the effectiveness of gas inflow stimulation works. A classification and analysis of prominent Russian and foreign meth-ods are provided and their issues are identified. As a result, the work refines the methodology for assessing the effectiveness of work at the drilling enter-prise. The authors’ comprehensive approach to assessing the effectiveness of inflow stimulation works, which allows for obtaining interrelated performance assessments, is proposed.